Field of dreams - Robinson, Phil Alden; Gordon, Lawrence; Gordon, Charles; Kinsella, W.P. ([Universal City, Calif.] Universal City Studio, 1989)
When Ray Kinsella hears a voice in his field and has a vision of a baseball field, he builds a baseball diamond in his cornfield. Soon players from the infamous 1919 Chicago "Black" Sox, led by Shoeless Joe Jackson, return to play in his field.
Based on the book "Shoeless Joe" by W. P. Kinsella.
VHS.
Written for the screen and directed by Phil Alden Robinson.
Kevin Costner, Amy Madigan, James Earl Jones, Ray Liotta, Burt Lancaster.
Keywords: Jackson, Joe -- 1888-1951.; Sports in motion pictures; Baseball films; Feature films; Fantasy films